Clinico-Pathology and Surgical Management of Leiomyosarcoma in Dog: A Case Report - Khandelwal, Priya; Singh Gurjar, Kuldeep; Mishra, Rakesh; Rathore, Annu; Kumar, Naveen (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A malignant smooth muscle tumour of mesenchymal origin, leiomyosarcoma can develop anywhere in the body. Smooth muscle is the site of this slow-growing, locally invasive, malignant tumour, which usually spreads slowly. Deep dermal smooth muscle, arrector pili, or vascular areas in the genital region can all give birth to dermal smooth muscle tumours (Enzinger et al., 2001). They are identified as angioleiomyomas and angio-leiomyosarcomas, pilo-leiomyomas and pilo-leiomyosarcomas, or genital leiomyomas and leiomyosarcomas, respectively (Liu and Mikaelian, 2003). Dermal smooth muscle tumours occur most frequently in dogs, cats and ferrets (Bahl et al., 2020). Surgical resection is the treatment most used for leiomyosarcoma. In humans and most other animals, leiomyosarcomas are relatively common in the visceral organs, especially the gastrointestinal tract and female genital tract, and in the spleen in dogs (Enzinger et al., 2001; Cooper and Valentine, 2002). Leiomyosarcoma rarely occurs in other organs; only a few cases in the oral cavity, oesophagus, and urinary bladder have been reported in humans and animals (Enzinger et al., 2001; Cooper and Valentine, 2002). Subcutaneous leiomyosarcoma is extremely rare in animals. This document puts on record a clinico-pathological study and surgical management of leiomyosarcoma in a dog.